Cerebellar involvement associated with immune checkpoint inhibitors: A systematic review. (17th November 2022) - Dinoto, Alessandro; Mantovani, Elisa; Ferrari, Sergio; Mariotto, Sara; Tamburin, Stefano
Abstract: Background and purpose: Immune checkpoint inhibitors (ICIs) targeting programmed death receptor 1 (PD‐1), cytotoxic T‐lymphocyte‐associated‐4 (CTLA‐4) and programmed cell death ligand 1 can be associated with immune‐related adverse events (iRAEs). Amongst neurological iRAEs, cerebellar involvement seems to be rare and currently lacks a proper characterization. The aim of this study was to phenotype cerebellar iRAEs. Methods: A systematic review was performed according to PRISMA guidelines including reported patients with cerebellar involvement related to ICIs and with available individual data. Results: After screening 2765 records, 32 studies with 46 patients were included. Median age was 63 years (20–82), and most patients were male (63.0%). Isolated cerebellitis was observed in 32.6% of cases, whilst the remaining cases had "cerebellitis plus", mostly associated with encephalitis/encephalopathy. Associated tumors included most frequently lung cancer, melanoma and Merkel cell carcinoma. PD‐1 inhibitor was the most administered treatment ( n  = 29, 64.4%), whilst exposure to CTLA‐4 inhibitor was rare ( n  = 2, 4.5%). Magnetic resonance imaging was abnormal in 43.2% of patients and inflammatory cerebrospinal fluid findings were frequently observed. Autoantibodies were detected in 61.9% of patients and included novel reactivities. Amongst treatment strategies, the most common were steroids ( n  = 36) and ICI discontinuation ( n  = 28, 90.3%). Relapses were reported in 10% of patients. Most patients showed improvement/remission ( n  = 31) but, at last follow‐up, 12 had died. Isolated cerebellitis versus cerebellitis‐plus differed in terms of outcomes, whilst seropositive versus seronegative patients had distinct tumor associations. Discussion: Cerebellar iRAEs are usually multifocal, have heterogeneous tumor associations, are most associated with PD‐1 inhibitor exposure and are related to autoantibodies, including novel reactivities.